Hydrophobic interpenetrating polyamide-PDMS membranes for desalination, pesticides removal and enhanced chlorine tolerance - Khairkar, Shyam R.; Pansare, V, Amol; Shedge, Amol A.; Chhatre, Shraddha Y.; Suresh, A. K.; Chakrabarti, Subhananda; Patil, Vishwanath R.; Nagarkar, Amit A. (Chemosphere, 2020)
Hydrophobic membranes for desalination and toxic organic pollutant removal have been fabricated using polyamide - PDMS (polydimethylsiloxane) chemistries in a one-step protocol. The curing of polyamide and PDMS are orthogonal and co-curing both networks imparts hydrophobicity to the thin film composite membranes. The membranes exhibit increased adsorption of pesticides from the feed water along with maintaining excellent salt rejection capability (97% NaCl rejection), thus giving the membranes a multifunctional character. Three toxic pesticides have been used in this study to demonstrate the viability of combining osmosis desalination technology with organic matter adsorption. The membranes also show excellent resistance to fouling by toxic pesticides (85% salt rejection vs 67% for commercial membranes in the presence of pesticides) and significantly improved chlorine tolerance (93.8% salt rejection vs 86.5% for commercial membranes after 20 h of exposure to sodium hypochlorite solution). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: PDMS (Polydimethylsiloxane); Pesticide rejection; Salt rejection; Water purification membranes

"Shape-coding'': morphology-based information system for polymers and composites - Pansare, V, Amol; Chhatre, Shraddha Y.; Khairkar, Shyam R.; Bell, Jeffrey G.; Barbezat, Michel; Chakrabarti, Subhananda; Nagarkar, Amit A. (ACS Applied Materials & Interfaces, 2020)
Fiber-reinforced composites have become the material of choice for aerospace structures because of their favorable strength-to-weight ratio. Given the increasing amounts of counterfeit composite parts showing up in the complex aerospace supply chain, it is absolutely vital to track a composite part throughout its lifecycle-from production to usage and to disposal. Existing barcoding methods are invasive, affect the structural properties of composites, and/or are vulnerable to tampering. We describe a universal method to store information in fiber-reinforced composites based on solid-state in situ reduction leading to embedded nanoparticles with controlled morphologies. This simple, cost-effective, mild, surfactant-free, and one-step protocol for the fabrication of embedded platinum nanostructures leads to morphology-based barcodes for polymeric composites. We also describe a coding methodology wherein a 1 x 1 cm code can represent 3.4 billion parts to 95 trillion parts, depending on the resolution required along with access to morphology-based chemical encryption systems.
Keywords: barcoding chemical encryption; epoxy composites; nanoparticle morphology control; solid-state synthesis